Environmental Diagnosis of Rio Araguaia Basin – From Barra do Garças (MT) to Luiz Alves (GO) - DOI 10.5216/bgg.v19i1.15343 - Del’Arco J., Oliveira; W.A. G., Rio; L.A, Dambrós; , I., Tarapanoff; A.S.S., Novaes (Boletim Goiano de Geografia, 2011)
.